The absence of an effect of nickel on iron isotope fractionation during core formation. (15th June 2022) - Kubik, E.; Sossi, P.A.; Siebert, J.; Inglis, E.; Roskosz, M.; Siciliano Rego, E.; Wehr, N.; Moynier, F.
Abstract: The Fe isotopic compositions of mantles of differentiated inner solar system bodies are similar to, or heavier than those of chondritic meteorites. Core–mantle differentiation is a potential contributor to planetary isotopic fractionation. However, previous metal–silicate experiments provide only equivocal evidence for such fractionation, and have been used to argue that the Ni content of core-forming metal influences the extent of Fe isotopic fractionation. Here, we complement existing data with twenty-two novel metal–silicate equilibrium experiments with varying Ni content to better quantify the effect of Ni on the vector and magnitude of Fe isotopic fractionation during core formation. We find no statistically resolvable effect of the Ni content in the metallic phase on the metal–silicate Fe isotopic fractionation factor over a wide range of Ni concentrations (0–70 wt.% in the metal). In particular, the Fe isotopic composition of alloys from two experiments performed with 70 wt.% of Ni (δ 56 Femetal  = 0.27 ± 0.04‰ and 0.32 ± 0.03‰, 2 standard deviations σ) are identical to the bulk experimental starting material (δ 56 Febulk  = 0.27 ± 0.10‰, 2σ). Our data across all experiments yield an average isotopic fractionation factor Δ 56 Femet–sil  = 0.05 ± 0.22‰ (2σ) at 1873 K and 1–2 GPa, suggesting that little to no isotopic fractionation of Fe is expected to occur during core formation at low pressures. As such, our data does not support core formation as the main mechanism causing the observed variability in Fe isotope ratios between the silicate Earth, Moon, Vesta and other differentiated asteroids. A combination of multiple accretion-related processes—including condensation from the solar nebula, volatile-depleting events such as giant impacts, and the disproportionation of ferrous iron to ferric iron and iron metal in larger bodies—as well as deep mantle and recycling processes could explain the heavier-than-chondritic signatures in the silicate Earth and Moon. Furthermore, our results support the ideality of mixing among Fe–Ni alloys, as previously demonstrated for physical properties but less conclusively evidenced for chemical properties.